A cross-dehydrogenative C(sp3)−H heteroarylation via photo-induced catalytic chlorine radical generation - Huang, Chia-Yu; Li, Jianbin; Li, Chao-Jun (Nature communications, 2021)
Hydrogen atom abstraction (HAT) from C( sp 3 )–H bonds of naturally abundant alkanes for alkyl radical generation represents a promising yet underexplored strategy in the alkylation reaction designs since involving stoichiometric oxidants, excessive alkane loading, and limited scope are common drawbacks. Here we report a photo-induced and chemical oxidant-free cross-dehydrogenative coupling (CDC) between alkanes and heteroarenes using catalytic chloride and cobalt catalyst. Couplings of strong C( sp 3 )–H bond-containing substrates and complex heteroarenes, have been achieved with satisfactory yields. This dual catalytic platform features the in situ engendered chlorine radical for alkyl radical generation and exploits the cobaloxime catalyst to enable the hydrogen evolution for catalytic turnover. The practical value of this protocol was demonstrated by the gram-scale synthesis of alkylated heteroarene with merely 3 equiv. alkane loading. Hydrogen atom abstraction from C( sp 3 )–H bonds of naturally abundant alkanes for alkyl radical generation represents a promising yet underexplored strategy in the alkylation reaction designs. Here the authors show a photo-induced and chemical oxidant-free cross-dehydrogenative coupling between alkanes and heteroarenes using catalytic chloride and cobalt catalyst.